Advances in genetic approaches for sustainable insect pest management - Asif, Muhammad Usman; Memon, Raza Muhammad (Journal of Pure and Applied Agriculture, 2025)
Insect pests have contributed significantly to agricultural losses as well as to the spread of vector born infectious diseases globally for the last two decades. Insecticides use is the most significant strategy among the farmers for pest management; however, this practice has been posing considerable hazards to population health and their surroundings. Additionally, extensive insecticide application has also contributed to resistance in a wide range of insect pests. Genetic pest mitigation strategy like sterile insect technique (SIT) has successfully eradicated various damaging pests globally. This technique is based on the mass release of genetically modified organisms into the ecosystem. However, sterilization by traditional methods declines the mating competitiveness and overall vitality of released sterile males. To overcome these limitations different sterility approaches i.e. release of insects carrying dominant lethal (RIDL), incompatible insect technique (IIT) utilizing Wolbachia and autosomal-linked X- chromosome shredders have also been proposed as a substitute to traditional SIT approach. Although these first-generation genetic SIT approaches signify considerable progress, each method has certain drawbacks. Thus, application of highly advanced SIT based approaches would be logistically beneficial that could efficiently separate sexes and at the same time sterilize males, while ensuring that their fitness will not be significantly affected. CRISPR has facilitated the establishment of innovative system called precision guided sterile insect technique (pgSIT) that allows concurrent sterilization and sexing, facilitates release of eggs and ensures emergence of sterile males. In the upcoming time, this technique could be utilized against both insect vectors responsible for transmission of human diseases and agricultural pests for reduction in prevalence of both human diseases and crop losses, respectively, thereby eliminating the necessity of dangerous synthetic chemicals and advancing insect pest management. This review briefly discusses all these SIT based approaches regarding their mechanisms, advantages, successful application against different target pests and drawbacks.